2019
DOI: 10.1093/hmg/ddz215
|View full text |Cite
|
Sign up to set email alerts
|

Individualized management of genetic diversity in Niemann-Pick C1 through modulation of the Hsp70 chaperone system

Abstract: Genetic diversity provides a rich repository for understanding the role of proteostasis in the management of the protein fold in human biology. Failure in proteostasis can trigger multiple disease states, affecting both human health and lifespan. Niemann-Pick C1 (NPC1) disease is a rare genetic disorder triggered by mutations in NPC1, a multi-spanning transmembrane protein that is trafficked through the exocytic pathway to late endosomes (LE) and lysosomes (Ly) (LE/Ly) to globally manage cholesterol homeostasi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 106 publications
(194 reference statements)
1
33
0
Order By: Relevance
“…It is not associated with increased risks of infections. 31 Previous studies have indicated the chronicity of the condition, and follow-up usually indicates the stability and benign nature of the condition. 32 Clinical history can also suggest the presence of other causes of neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…It is not associated with increased risks of infections. 31 Previous studies have indicated the chronicity of the condition, and follow-up usually indicates the stability and benign nature of the condition. 32 Clinical history can also suggest the presence of other causes of neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…A cloned cDNA construct of NPC1, named NPC1 WT‐V that has been used as wild‐type NPC1 in publications by us and others, also contains four variants in comparison to the Genbank reference sequence . These variants are 387 T>C (Y129Y), 1415 T>C (L472P), 1925 T>C (M642T) and 2587 T>C (S863P).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study examined the effects of modulating the HSP70 chaperone/co-chaperone complex on a large number of NPC1 variants (14). That study focused on the effects of an allosteric inhibitor, JG98, that alters the interactions of HSP70 with co-chaperones, especially the BAG family of co-chaperones (73,74).…”
Section: Discussionmentioning
confidence: 99%
“…Boosting chaperone activity has been proposed as a method to correct the defect in NPC1 mutant cells (12,(24)(25)(26). Changes in molecular chaperone activity are one of the many consequences of HDACi treatment (14,27,28). A quantitative proteomic analysis of the response to HDACi in NPC1 human fibroblasts revealed that the expression of proteins associated with protein folding was modulated (29).…”
Section: Introductionmentioning
confidence: 99%